Owidiusz, Amory III 1 w polskim przekładzie - Wesołowska, Elżbieta (Collectanea Philologica, 2023)
The paper aims to show the new Polish translation with a brief introduction. The elegy seems to be especially interesting as the way of poetical recusatio and the sophisticated game with the reader.